Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1017/s0022377819000448
|View full text |Cite
|
Sign up to set email alerts
|

Wave dispersion in pulsar plasma. Part 2. Pulsar frame

Abstract: Wave dispersion in a pulsar plasma is discussed emphasizing the relevance of different inertial frames, notably the plasma rest frame K and the pulsar frame K ′ in which the plasma is streaming with speed β s . The effect of a Lorentz transformation on both subluminal, |z| < 1, and superluminal, |z| > 1, waves is discussed. It is argued that the preferred choice for a relativistically streaming distribution should be a Lorentz-transformed Jüttner distribution; such a distribution is compared with other choices… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(70 citation statements)
references
References 22 publications
(47 reference statements)
5
65
0
Order By: Relevance
“…This is one of the main differences from the works of Rafat, Melrose & Mastrano (2019 a ) and Rafat et al. (2019 b ), who analysed the dispersion properties of subluminal waves for arbitrary Lorentz factor of the wave phase velocity . The authors showed that there is a sufficiently large range of values of , in which there is a good agreement with the results of Beskin et al.…”
Section: Description Of the Problemmentioning
confidence: 74%
See 4 more Smart Citations
“…This is one of the main differences from the works of Rafat, Melrose & Mastrano (2019 a ) and Rafat et al. (2019 b ), who analysed the dispersion properties of subluminal waves for arbitrary Lorentz factor of the wave phase velocity . The authors showed that there is a sufficiently large range of values of , in which there is a good agreement with the results of Beskin et al.…”
Section: Description Of the Problemmentioning
confidence: 74%
“…1988, (2.17) 1 ; Rafat et al. 2019 b , (6.17)) On the other hand, for we have (see below). Indeed, for low number density (when ), i.e.…”
Section: Description Of the Problemmentioning
confidence: 85%
See 3 more Smart Citations